Spray-drying of Dunaliella salina to produce a β -carotene rich powder - Leach, G. (2011)
Powders of Dunaliella salina biomass were obtained by spray drying a cell concentrate under different drying regimes. A three-factor, two-level experimental design was employed to investigate the influence of inlet temperature, outlet temperature and feed solids on b-carotene recovery. The effect of microencapsulation in a polymer matrix of maltodextrin and gum arabic was also studied. All powders were stored under specific conditions to assess the stability of the native b-carotene. There was a trend indicating that lower outlet temperature yielded higher carotenoid recoveries, b-carotene recovery varying between 57% and 91%. Microencapsulated biomass yielded 100% recoveries. All non-microencapsulated powders were unstable in terms of b-carotene content in the presence of natural light and oxygen showing 90% degradation over a 7-day period. The incorporation of a microencapsulating agent had a significant increase in the storage stability. Results indicated a first-order degradation of the b-carotene in microencapsulated powders with kinetic constants of 0.06 day-1 and 0.10 day-1. HPLC analysis showed no effect of drying processes on isomer composition (9-cis-b-carotene and all-trans-b-carotene ratio). This behaviour was also observed during storage of the microencapsulated powders.